Penerapan konsep hari derajat tumbuh untuk menentukan jadwal panen mangga yang optimal di Situbondo - Pramudia, Aris; Affandi; Marta, Nini (Innovation Centre for Tropical Sciences, 2024)
Determining the optimal harvest time for an agricultural commodity can be achieved by applying the concept of growing degree days (GDD). The purpose of this research is to determine the potential time of flowering to harvest, especially in developing Arumanis 143 mango cultivation off-season. The study was conducted at the Arumanis 143 mango plantation, owned by PT. Trigatra Rajasa, in Ketowan Village, Arjasa District, Situbondo Regency. The simulation method used in this research was calculating the cumulative GDD using daily average temperature data and the base temperature of mango at 10 °C. The simulation assumed a cumulative value of 543ºC at the beginning of the flowering phase, a value of 945ºC at the beginning of the fruiting phase, and a value of 2,942ºC at the harvest time for export quality. The simulation results indicated that during on-season conditions, mango flowers usually appeared between the third 10 days of May to the third 10 days of June (May III-June III), originating from shoots that emerged between April III to May III. The fruit emergence was estimated to occur around June II-July II, and harvest time around October II-November II. In off-season conditions, the initial emergence of shoots, flowers, fruit, and mango harvest was estimated to occur sequentially around March I-III, April I-III, April III-May II, and August III-September II. The simulation results suggested that the duration of fruiting is longer (20-30 days) compared to existing conditions, resulting in a delay of 20-30 days in fruit harvesting. This research emphasizes the importance of identifying the correct harvest time based on the growth phenology of Arumanis 143 mango plants. Keywords: fruiting duration, growing degree days, harvest time, mango